ASSESSMENT OF RIPARIAN VEGETATION PATTERN ALONG ALISTA HILLY RIVER BASIN - Parmawati, Rita; Rokani, Lutvita Erya; Yakub, Arham; Riarmanto, Arief Kurnia; Pertiwi, Maya; Hidayat, Herman; Kurnianto, Agung Sih (Journal of Tropical Life Science, 2018)
Riparians are undergoing extensive reductions and changes in their natural composition into agricultural and urban area. The relationship between the vegetation distribution pattern and the riparian topography factor has been assumed to typically represent a biome-specific or vegetation-specific constant. This study aim is to analyze the vegetation distribution pattern with topography along Alista river in Dau District, Malang. We surveyed 3 stations that represent a zone of edge gradient between the river and the mainland: levee, mid-flood, and slough. We used the wetland classification (Obligate - OBL; Facultative Wetland-FACW; Facultative Upland (FACU); and Upland (UPL) for each species found from various sources. we observed that facultative upland plants have a broad dominance. Mid-floodplain and slough dominated by typical upland species. Although Levee widely consisted of by upland plants, this area has one distinctive obligate species: Equisetum. The presence of OBL species in the levee and mid-floodplain indicate the area is receiving more frequent floods than other areas.